Development of the Hutaraja Village hot springs tourist attraction as a sustainable tourism destination - Rezki Aulia; Muhammad Hafif Yadi; Indra Muda; Hadi Rudiya; Agus Wiranto (Privietlab, 2025)
Hutaraja Hot Springs is a natural hot spring with crystal clear water originating from Mount Sorik Merapi. In addition to pure water, the water contains sulfur, which is beneficial for health. Surrounded by rice fields and community plantations, this tourist attraction is even more beautiful and charming than it already is. If managed properly, it will certainly be beneficial for improving the community's economy and increasing the original income of the Hutaraja village from the tourism sector. This study aims to determine the efforts to develop Hutaraja hot spring as a sustainable tourism destination. The research method used is qualitative with descriptive data. Data collection techniques included direct observation of the Hutaraja hot spring tourist attraction, accommodation to the location, supporting facilities around the tourist attraction, and direct involvement of stakeholders and the local community in the development of the Hutaraja hot spring, and documentation studies. In-depth interviews were conducted with the Mandailing Natal Regency Tourism Office, Mandailing Natal Regency Bappeda Office, Panyabungan Sub-district Head, Head of South Hutaraja Village, local community, food vendors/stalls, and visitors. The study results show that efforts to develop the Hutaraja hot spring tourist attraction as a sustainable tourism destination were carried out by considering five aspects, namely Attraction, Accessibility, Accommodation, Amenities, and Ancillary services (the 5A tourism concept). The conclusion is that development efforts that consider the 5A tourism concept have proven effective in increasing visitor numbers, as evidenced by the thousands of visitors to the tourist attraction each year and the relatively stable upward trend in visitor numbers.